Validation of a malodour‐forming enzyme as a target for deodorant actives: in vivo testing of a glutamine conjugate targeting a corynebacterial Nα‐acyl‐glutamine‐aminoacylase1. (3rd February 2013) - Natsch, Andreas; Joubert, Caroline; Cella, Mauricio; Flachsmann, Felix; Geffroy, Cedric; Natsch, Andreas
ABSTRACT The chemical structure of human body odorants and the enzymatic pathways for their release from amino acid conjugates by skin bacteria have been elucidated in recent years. These findings open up theoretical avenues for an added layer of malodour prevention by blocking the cleavage of malodour precursors. Previously, we had validated in vitro an alternative substrate that releases a fragrance molecule instead of a malodour acid upon the action of a corynebacterial Nα‐acyl‐glutamine‐aminoacylase. In order to assess whether this concept delivers a perceivable reduction of malodour in vivo, a number of studies were performed: (1) a controlled clinical study with expert assessment, (2) a blinded study with consumer self‐assessment of a placebo versus an active formulation in left–right comparison, and (3) a longitudinal consumer study comparing two doses of the active versus a placebo formulation. A statistically significant benefit for malodour reduction was observed in all three studies, this benefit consistently seen on panellists with a higher self‐ or expert‐perceived malodour, whereas there was no difference in panellists with a lower level of malodour formation. In addition, malodour formation was higher in panellists with noticeable cleavage of the alternative substrate, indicating a correlation between enzyme activity and malodour levels. These results indicate that the targeted enzyme is a relevant source of malodour on panellists suffering from strong body odour, and that malodour reduction on these panellists is possible by specifically targeting this enzyme. Whereas the absolute reduction of malodour with the tested substrates was relatively small, the studies presented here clearly validate Nα‐acyl‐glutamine‐aminoacylase as a target for deodorant actives, and they demonstrate that a significant benefit can be achieved especially in individuals developing stronger axillary odour. Copyright © 2013 John Wiley & Sons, Ltd.